Review and evaluation of the proposed wireless mesh routing protocols - Senan Mahmod, Zainab; Hassan Abdalla Hashim, Aisha; Al-Irhayim, Sufyan; Khan, Sheroz (Faculty of Engineering, International Islamic University Malaysia, 2008)

(untitled)
Wireless mesh networks (WMNs) have emerged as a key technology for next-generation wireless networking. Because of their advantages over other wireless networks, WMNs are undergoing rapid progress and many exciting applications. Although WMNs can be built up based on existing technologies, field trials and experiments with existing WMNs prove that the performance of WMNs is still far below expectations. Therefore, several challenging research were made to develop and improve the performance. This paper presents networking routing protocols proposed for WMNs. Performance analysis is shown, performance metrics considered are routing over head and packet delivery ratio. An evaluation summary was presented